Local Government Responsibility in Ensuring Legal Protection for Teachers: A Case Study of Jambi Province - Hartati Hartati; Ratna Dewi; Ivan Fauzani Raharja; Dimas Subekti (Indonesian State Law Review (ISLRev), 2026)
This study examines the role of the Jambi Provincial Government in providing legal protection for teachers in performing their professional duties. Using a combined normative and empirical legal approach, the study finds that legal protection remains structurally weak due to the absence of local regulations, lack of legal aid institutions, and poor inter-agency coordination. These conditions create legal uncertainty and contribute to a “culture of legal fear” among teachers. The study proposes a regional-based legal protection model involving regulatory reform, institutional strengthening, and cross-sectoral coordination. This model contributes to the development of responsive governance and reinforces the implementation of substantive regional autonomy.